Modelling size constraints on carbonate platform formation in groundwater upwelling zones. Issue 1 (December 2018) - Keppel, Mark; Post, Vincent; Love, Andrew; Werner, Adrian; Clarke, Jonathan; Halihan, Todd
Abstract Carbonate depositional systems related to groundwater upwelling are ubiquitous around the world and form ecologically and culturally important features of many landscapes. Spring carbonate deposits record past climatic and hydrological conditions. The reconstruction of past processes using spring carbonate proxies requires fundamental understanding of the factors that control their geometry. In this work, we show that the spatial extent of spring carbonate platforms is amenable to quantitative prediction by simulating the early growth stage of their formation for the iconic mound springs in the central Australian outback. We exploit their well-defined, circular geometry to demonstrate the existence of two size-limiting regimes: one controlled by the spring flow rate and the other by the concentration of lattice ions. Deviations between modelled and observed size metrics are attributable to diminishing spring flow rates since formation, enabling assessment of the relative vulnerability of springs to further hydrological change.